Oral Health of Bangladeshi Women Tobacco-with-paan Users and Self-re-p orted Oral Pain Following- Tobacco Cessation - Ray Croucher, PhD; Allan K. H. Pau, BDS, MSc; Matt Jerreat, BDS; Shamsia Begum, BA; (Blackwell Synergy, 2003)
The study objectives were to assess the oral health status of a sample of UK resident Bangladeshi women tobacco-in-paan users and its relationship to participant age and number of daily paan, to determine the prevalence of oral pain at baseline and at the one-week postcessation follow-up, and to explore the relationship between oral health status and changes in self-reported oral pain at baseline and at the one-week postcessation fol/ow-up